Product Market Peers in Lending - De Franco, Gus; Edwards, Alexander; Liao, Scott (Management Science, 2021)
This study examines how product market peers affect lending relationships. We contend that firms are more likely to borrow from a bank that has previously lent to a peer to mitigate information asymmetry with the bank when potential information processing efficiencies are greater (i.e., information efficiency hypothesis), but there will be a decreased propensity to borrow from a shared lender when the costs of leaking proprietary information are greater (i.e., proprietary information leakage hypothesis). We find that, after bank mergers that involve peers’ lenders, firms are more likely to switch banks to avoid sharing the same lenders as a product market peer. In cross-sectional analyses, we find that after bank mergers that involve a peer’s bank, firms are less likely to switch when the firm’s financial reporting is more opaque and has greater monitoring needs, consistent with the information efficiency hypothesis. In contrast, firms are more likely to switch after bank mergers that involve a peer’s bank when the firm belongs to an industry with greater proprietary costs and when the bank has greater incentives to leak information, consistent with the proprietary cost hypothesis. This paper was accepted by Brian Bushee, accounting.